Controllability attributions and relationship closeness in idiocentric and allocentric youths’ willingness to help a suicidal peer. - Chen, Jo-Ann Yu'En. (2011)
The study’s main aim was to investigate if an individual’s cultural orientation (idiocentrism or allocentrism) would lead to different situational factors (controllability attributions or relationship closeness) having more of a significant influence on a youth’s willingness to help a suicidal peer. To test this, 100 Singaporean university undergraduates participated in an online survey. The study found that a strong effect of relationship closeness regardless of cultural orientation. In contrast, controllability attributions appeared to have little influence on helping behaviours in general. The implications of results for the development of a peer helping programme is discussed.